lncRNA Panct1 maintains mouse embryonic stem cell identity by regulating TOBF1 recruitment to Oct-Sox sequences in early G1 - Chakraborty, Debojyoti; Paszkowski-Rogacz, Maciej; Berger, Nicolas; Ding, Li; Mircetic, Jovan; Fu, Jun; Iesmantavicius, Vytautas; Choudhary, Chunaram; Anastassiadis, Konstantinos; Stewart, A. Francis; Buchholz, Frank (Cell reports, 2017)
Long noncoding RNAs (lncRNAs) have been implicated in diverse biological processes, including embryonic stem cell (ESC) maintenance. However, their functional mechanisms remain largely undefined. Here, we show that the lncRNA Panct1 regulates the transient recruitment of a putative X-chromosome-encoded protein A830080D01Rik, hereafter referred to as transient octamer binding factor 1 (TOBF1), to genomic sites resembling the canonical Oct-Sox motif. TOBF1 physically interacts with Panct1 and exhibits a cell-cycle-specific punctate localization in ESCs. At the chromatin level, this correlates with its recruitment to promoters of pluripotency genes. Strikingly, mutating an octamer-like motif in Panct1 RNA abrogates the strength of TOBF1 localization and recruitment to its targets. Taken together, our data reveal a tightly controlled spatial and temporal pattern of lncRNA-mediated gene regulation in a cell-cycle-dependent manner and suggest that lncRNAs might function as barcodes for identifying genomic addresses for maintaining cellular states.